1911 Wash. Sess. Laws 303, An Act Relating to the Carrying of Firearms, Requiring Licenses of Certain Persons, and Fixing a Penalty for the Violation Thereof, ch. 52, § 1 - (:unkn) unknown (My University, 1911)
Required noncitizens to receive a license from the state auditor, upon a certificate from the consul of the individuals' country of origin and payment of a fee, before noncitizen can possess a firearm.
Keywords: POSSESSION - DANGEROUS PERSONS; REGISTRATION